Chronic valproate or levetiracetam treatment does not influence cytokine levels in humans - Guenther, Sabina; Bauer, Sebastian; Hagge, Mareike; Knake, Susanne; Olmes, David G.; Tackenberg, Bjoern; Rosenow, Felix; Hamer, Hajo M. (Seizure-European Journal of Epilepsy, 2014)
There is growing evidence that complex interactions between seizures and the immune system shape the course of epilepsy. However, systematic analyses of the effects of antiepileptic drugs (AED) on the immune system in humans are rare. We performed a prospective study on the influence of the widely used AED valproate and levetiracetam on interictal immunological parameters.36 patients were prospectively included. 15 were started on valproate (5 female (33%), age 54±27 years, 12 (80%) on monotherapy), 21 on levetiracetam (10 female (48%), age 45±19 years, 17 (81%) on monotherapy). Before treatment and after 3 months, we performed a differential blood count and analyzed the distribution of CD3(+)CD4(+)-, CD3(+)CD8(+)- and CD4(+)CD25(+)-leukocyte subsets using flow cytometry. In addition, we determined the concentrations of IL-1?, IL-6, TNF-? and MCP-1 in the peripheral blood using ELISAs.Valproate intake resulted in a significant decrease of the total white blood count (6.96±1.23/nl vs. 6.13±1.57/nl, p=0.026) and of absolute count and percentage of neutrophils (4.60±1.05/nl vs. 3.69±1.30/nl, p=0.01; 65.4±7.9% vs. 59.5±11.5%, p=0.01, respectively). The percentage of CD3(+)CD4(+)-lymphocytes dropped significantly (50.4±10.9% vs. 45.3±12.3%, p=0.002). Levetiracetam treatment resulted in a decrease of the percentage of CD4(+)CD25(+)-lymphocytes (26.1±8.0% vs. 21.5±9.2%, p=0.01) but did not significantly alter absolute counts. Neither valproate nor levetiracetam were associated with significant changes in cytokines.Valproate intake results in profound changes of white blood cell count and subset distribution. Cytokine levels were not influenced by valproate or levetiracetam.
EVALuna2:22288